Evidence for Resilient Agriculture R-packages (ERAg and ERAgON) - Steward, Peter Richard; Joshi, Namita; Rosenstock, Todd Stuart (2023)
ERAg package containing the ERA dataset, bibliography, search terms and various vignettes and functions for processing and analyzing ERA data. Please use browseVignettes("ERAg") for vignettes that will guide you through the contents of this package. ERAg is complimented by the ERAgON package which links ERA observations to climate, soils and topographical information.